The Guild of Nurses is proud of its achievements in 1938 (leaflet) (London : Guild of Nurses, 1939)
1939 1939 1930s 4 pages F NURSES The saving of life is a mysterious and fascinating craft, and when once she is master of her profession a nurse finds in her work a satisfaction that can only be really understood by those who have experienced it. WHAT OF THE GUILD? The GUILD OF NURSES is definitely a professional and vocational organisation, controlled entirety by experienced members of the nursing profession for all those engaged therein. It is the nursing services section of its parent body, the National Union of County Officers, affiliated to the T.U.C., the body which has done so much in attempting to find the remedy for improving the professional status and conditions of employment of nurses. The Guild is non-political and has no strike clause, neither would it countenance any such policy in respect of those who are obliged to give care, sympathy and attention to the sick and needy. The bogey of "strikes" is always raised by those who are opposed to the proper development and protection of your professional interests, for the reason that the "powers that be," are desirous of keeping the control of the alleged "protective" organisations in their own hands — to the ultimate detriment of the members thereof. The Guild is a democratic institution, with no class or grade distinctions. The members control. The member is the chief concern. Their requirements are served. [photograph] For this she will bear without complaining duties and conditions of work which would seem hardly tolerable set down in print. Trustees: Mr. F.G. GILLINGHAM Legal Advisers: Mr. E. RIDLEY, O. B. E., LL. B., Barrister-at-Law, and Mr. R. HERLIGHY, Barrister-at-Law. Solicitors: Messrs. STUTFIELD AND SON. General Secretary: G. VINCENT EVANS, F.C.I.S. National Organiser: Councillor Mrs. B.M. DRAPPER, J.P. Organising Sec. Mrs I. BROOK, S.R.N., S.C.M. Head Office 38, Argyle Square, Kings Cross London, W. C. 1. Telephone: Terminus 1102/3. DISTRICT REPRESENTATIVES Gateshead .. Mr G.C. ESTHER, 9, Appian Place, Sheriff Hill. Leeds .. Councillor W. WEBSTER, J. P., 89, Hunslet Hall Road, Leeds, 11. Manchester .. Alderman E.A. HARDY, J.P., Bank Chambers, 287, Broad Street, Salford. Midland .. Mr. J.L. KIND, 358, Shobnall Street, Burton-on-Trent. South Wales .. Mr. T.O. MORGAN, S.R.N., 78, Penarth Road, Grangetown, Cardiff. Bristol .. Mr. P. SAGE, 76, Mendip Road, Bristol, 3. Norwich .. Mr. B.J. SHARMAN, 28, St. Phillips Road, Norwich. (NOTE. — Personal interviews will be welcomed at any time. To avoid disappointment, please write for an appointment. All letters to be addressed to the General Secretary. Confidence in every matter strictly preserved yourself — ill be fair tients Why not NURSES? 292/54.73/2/3